Coaching' small biotech companies into success: The value-adding function of VC - Terttu Luukkonen; Mari Maunula (The Research Institute of the Finnish Economy (ETLA), 2006)
The paper reports an empirical study on the non-financial value-added provided by Venture Capital investors to their investee firms. This study will use a four-class grouping of the various non-financial value-adding capabilities provided by VC firms, namely, scouting, monitoring, signalling and value-adding services. The study examines biotechnology industry in Finland. Finland has a dual system with independent (partially ever-green) VC companies and public or semi-public VC organisations. Additionally, informal VCs are fairly active. Whether the different types of VC organisation aim, are able and indeed do deliver nonfinancial value-added, in addition to their financial input, is the central focus of this study. The paper has an evolutionary perspective on Venture Capital according to which VC promotes a variety of experimentation with new technologies, especially through the foundation of new firms oriented to experimentation and development of new ideas. At the same time, VC industry fulfils a selection function in its role as a financial intermediary. The study data have been collected through interviews, conducted at the end of 2005, with the total population of small and medium-sized, VC-backed biotech companies established in Finland since 1986. Central findings of the study include an observation that all three VC types did provide value-added in the meaning outlined above. Nevertheless, there were clear differences between them in terms of the overall perceived value-added as well as in their activity profiles. Informal investors were found to have the highest overall value-added and kept closest contacts with their investee firms.
Keywords: O16; G24; O38; L65; 330; Venture Capital; Biotechnology; Biotechnische Industrie; Risikokapital; Betriebliche Wertschöpfung; Unternehmensplanung; Finnland